Zhaonella formicivorans gen. nov., sp. nov., an anaerobic formate-utilizing bacterium isolated from Shengli oilfield, and proposal of four novel families and Moorellales ord. nov. in the phylum Firmicutes. Issue 5 (29th April 2020) - Lv, Xiao-meng; Yang, Min; Dai, Li-rong; Tu, Bo; Chang, Chen; Huang, Yan; Deng, Yu; Lawson, Paul A.; Zhang, Hui; Cheng, Lei; Tang, Yue-qin
Abstract : A novel obligately anaerobic, thermophilic and formate-utilizing bacterium K32 T was isolated from Shengli oilfield of China. Cells were straight rods (0.4–0.8 µm × 2.5–8.0 µm), Gram-stain-positive, non-spore-forming and slightly motile. Optimum growth occurred with pH of 7 and 0.5 g l –1 NaCl under temperature of 55–60 °C. Nitrate could be reduced into nitrite, syntrophic formate oxidation to methane and carbon dioxide occurred when co-culturing strain K32 T and Methanothermobacter thermautotrophicus ΔH. The main cellular fatty acids were iso-C15 : 0 (24.0 %), anteiso-C15 : 0 (21.7 %), C16 : 0 (12.7 %) and C14 : 0 (10.8 %), and the main polar lipid was phosphatidylglycerol. The G+C content of the genomic DNA was 46.3 mol%. The 16S rRNA gene sequence of K32 T shared ≤90.4 % of sequence similarity to closest type strains of Desulfitibacter alkalitolerans, Calderihabitans maritimus and members of the genus Moorella . Based on the phenotypic, biochemical and genotypic characterization, Zhaonella formicivorans gen. nov., sp. nov. is proposed with K32 T (=CCAM 584 T =DSM 107278 T =CGMCC1.5297 T ) as the type strain, which is the first representative of Zhaonellaceae fam. nov. In addition, the order Thermoanaerobacterales a nd family Peptococcaceae were reclassified, and three novel families in the novel order of Moorellales ord. nov. were also proposed.